Community-based seroprevalence of SARS CoV-2 in an urban district of Karachi, Pakistan - Muhammad Imran Nisar; Mashal Amin; Nadia Ansari; Farah Khalid; Najeeb Rehman; Aneeta Hotwani; Usma Mehmood; Arslan Memon; Junaid Iqbal; Ali Faisal Saleem; Daniel B. Larremore; Bailey Fosdick; et al. (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Antibody-based serological tests which target households and communities can estimate the true extent of infection in a population. It minimizes the biases of facility-based selective testing and generates scientific data on disease transmission through household asymptomatic cases. The objective of this study was to determine the seroprevalence and trend of SARS-CoV-2 in a densely populated urban community of Karachi. # Methods Three serial cross-sectional surveys were conducted in November 2020, February 2021, and December 2021 in Karachi's District East. Households were selected to provide serum samples for Elecsys® immunoassay for the detection of SARS-CoV-2 antibodies. All household members were eligible to participate regardless of age and infection status. Bayesian regression was used to adjust for assay performance and estimate seroprevalence. # Results We enrolled 1506 participants from 501 households. In November 2020, adjusted seroprevalence was estimated as 24.0% (95% confidence interval, CI=18.0-31.0), compared to 53.9% (95% CI=45.5-63.2) in February. In December 2021, it increased to 84.9% (95% CI=78.5-92.3). The conditional risk of infection was 41% (95% CI=29.9-51.6), 56.7% (95% CI=50.4--62.6) and 77.8% (95% CI=73.0-81.7) in surveys 4, 5, and 6 respectively. Only 18.7% of participants who had reactive antibodies for COVID-19 were symptomatic. # Conclusions An increase in seroprevalence estimates in Karachi's District East was observed over time. Community-based seroprevalence studies help to estimate the true proportion of the population that has been infected and predicts the spread of the disease in similar settings.